Pengaruh Debt To Equity Ratio (DER), Return On Equity (ROE), dan Earning Per Share (EPS) Pada Indeks Saham Syariah - Diah Ayu Nawang Wulan; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to examine the effect of Return On Equity (ROE), Deb to Equity Ratio (DER), and Earning Per Share (EPS) which are several financial ratios used to see a company's performance effectively and efficiently. Withdrawal of research samples using purposive sampling. The sample used is 10 issuers in the Islamic consumer goods industry sector on the Indonesia Stock Exchange (IDX) for the period 2019 to 2021 with a secondary data source in the form of annual financial reports. This study discusses the extent to which the financial ratios of these Islamic issuers affect stock prices so that they are expected to contribute to future investor analysis and decision making in investing and improving company performance in the future. By using multiple linear analysis method, the results of the study simultaneously show that ROE, DER and EPS have a significant effect on stock prices. Meanwhile, the partial test results show that only ROE and DER have no significant effect on stock prices, while the EPS ratio has a significant effect on stock prices. Therefore, Islamic issuers must maintain company performance, especially in generating profits. Profit achievement is the main indicator of investor interest in investing which will affect sharia stock prices to rise and have positive prospects.